2021
DOI: 10.3390/nano11051247
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect and Cellular Uptake Mechanism of Carbon Nanodots in in Human Microvascular Endothelial Cells

Abstract: Cardiovascular disease (CVD) has become an increasingly important topic in the field of medical research due to the steadily increasing rates of mortality caused by this disease. With recent advancements in nanotechnology, a push for new, novel treatments for CVD utilizing these new materials has begun. Carbon Nanodots (CNDs), are a new form of nanoparticles that have been coveted due to the green synthesis method, biocompatibility, fluorescent capabilities and potential anti-antioxidant properties. With much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 69 publications
(83 reference statements)
3
9
0
Order By: Relevance
“…In this context, our results present, for the first time, direct evidence that CNDs can enter EA.hy926 endothelial cells at a concentration as low as 0.03 mg/mL. Our research group recently demonstrated that endocytosis involves CND uptake by human microvascular endothelial cells [54]. However, there may be other routes of absorption.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…In this context, our results present, for the first time, direct evidence that CNDs can enter EA.hy926 endothelial cells at a concentration as low as 0.03 mg/mL. Our research group recently demonstrated that endocytosis involves CND uptake by human microvascular endothelial cells [54]. However, there may be other routes of absorption.…”
Section: Discussionsupporting
confidence: 65%
“…In the current study, EA.hy926 cells treated with CNDs for 24 h significantly increased NQO1 activity in EA.hy926 endothelial cells (Figure 6), which may be due to the longer exposure time. The possible reason why CNDs did not increase NQO1 gene expression in our previous study [54] in HMEC cells after 6 h of exposure was that the exposure time was short. It is also important to note that EA.hy926 and HMEC-1 cell lines have distinct transcriptomic profiles [86] and previous studies have suggested that these endothelial cells may have similar phenotypes but may respond differently to compounds such as the senolytic drug ABT-263 [87].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…TNF- α induction can increase ROS levels in endothelial cells [ 85 ]. Belperain et al reported the beneficial effects of carbon nanodots on TNF- α -induced ROS levels and inflammatory molecules in human microvascular endothelial cells [ 86 ] ( Table 1 ). Likewise, the modulating effects of cerium-doped carbon nanodots on inflammation during the course of wound healing have also been reported in a mouse model.…”
Section: In Vitro and In Vivo Studiesmentioning
confidence: 99%
“…In addition, the cell viability assessment confirmed the negligible toxicity of these materials in cells. An eco-friendly route was used to obtain Carbon Nanodots (CNDs), assessing their anti-inflammatory effects on Human Microvascular Endothelial Cells (HMEC-1) by Belperain et al [ 9 ]. Using non-cytotoxic concentrations (0.001, 0.03, 0.1, 0.3, 0.6, and 1.2 mg/mL), a reduction in pro-inflammatory cytokines, such as Interleukin-8 (IL-8) and Interleukin 1 beta (IL-1β) was demonstrated.…”
mentioning
confidence: 99%